A base promoted multigram synthesis of aminoisoxazoles: valuable building blocks for drug discovery and peptidomimetics. Issue 31 (8th March 2016) - Chalyk, Bohdan A.; Kandaurova, Inna Y.; Hrebeniuk, Kateryna V.; Manoilenko, Olga V.; Kulik, Irene B.; Iminov, Rustam T.; Kubyshkin, Vladimir; Tverdokhlebov, Anton V.; Ablialimov, Osman K.; Mykhailiuk, Pavel K.
Abstract : An easy access to a large panel of aminoisoxazoles starting from commonly available amino acids. Abstract : A practical multigram metal free synthesis of isoxazole-containing building blocks from commercially available amino acids was elaborated. The key reaction was a regioselective [3 + 2]-cycloaddition of in situ generated nitrile oxides with alkynes/enamines. The obtained building blocks were used in the preparation of bioactive compounds and peptidomimetics.